The Principal’s Policy on Optimizing the Cultivation of Religious Practices Among Students at MA Darul Ulum Semarang - Gentur Zarkasi Nur El Ihsan; Wahyudi Wahyudi (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the principal's policy in optimizing students' habituation to religious activities at MA Darul Ulum Semarang. The habituation of religious activities is one of the strategic efforts to internalize religious values in students' daily lives and to strengthen the religious culture within the madrasa environment. In the context of Islamic education, the principal plays a central role in formulating, directing, implementing, and evaluating policies that support the sustainable implementation of religious activities. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation. The collected data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the principal's policies play a significant role in fostering a religious culture among students through systematic program planning, teacher role modeling, and the provision of adequate facilities and infrastructure. Religious programs implemented regularly encourage students to engage in religious practices and facilitate the internalization of Islamic values in their daily lives. However, the implementation of these policies has not been fully optimal due to the gap between program planning and the internalization of religious values among students. The effectiveness of religious habituation is also influenced by the synergy among principals, teachers, students, and parents. The lack of alignment between the school and family environments remains one of the main obstacles to the internalization of religious values promoted through madrasa programs. In addition, variations in students' participation levels and inconsistencies in supervision affect the success of the planned programs. Therefore, transformational leadership is needed to strengthen the sustainable integration of religious values within the madrasa education system, ensuring that religious habituation is not merely carried out as a routine or formal activity but also generates a significant impact on students' religious awareness, attitudes, and behaviors. Keywords: Principal policy; religious culture; student habituation; student character; transformational leadership